The Formation and Drug Resistance Mechanism of Biofilm for Streptococcus pneumoniae Infection in Severe Respiratory Patients: Biofilm for Streptococcus pneumoniae in severe respiratory - Sun, Haiyan; Chai, Xinlou; Xu, Guangxun; Wei, Shuangying (Cellular and Molecular Biology, 2023)
This study was to explore whether Streptococcus pneumoniae would form biofilms and the formative factors of biofilms, as well as the drug resistance mechanism of S. pneumoniae. In this study, a total of 150 strains of S. pneumoniae were collected from 5 local hospitals in the past two years, and the minimum inhibitory concentrations (MIC) of levofloxacin, moxifloxacin and penicillin were determined by agar double dilution method to select the drug-resistant strains. The polymerase chain reaction (PCR) amplification and sequencing were performed on specific genes of drug-resistant strains. In addition, 5 strains of S. pneumoniae with penicillin MIC ≤ 0.065 μg/mL, 0.5 μg/mL, 2 μg/mL, ≥ 4μg/mL were randomly selected, and the biofilms were cultured on two kinds of well plates for 24 hours. Finally, whether the biofilms were formed was observed. Experimental results revealed that the resistance rate of S. pneumoniae to erythromycin in this area was as high as 90.3%, and the strains that were resistant to penicillin account for only 1.5%. The amplification and sequencing experiment revealed that one (strain 1) of the strains, which was resistant to both drugs, had a GyrA mutation and ParE mutation, and strain 2 had a parC mutation. All strains generated biofilms, and the optical density (OD) value of penicillin MIC ≤ 0.065 μg/mL group (0.235 ± 0.053) was higher than that of 0.5 μg/mL group (0.192 ± 0.073) (P< 0.05) and higher than the OD value of the 4 μg/mL group (0.200 ± 0.041) (P< 0.05), showing statistically great differences. It was confirmed that the resistance rate of S. pneumoniae to erythromycin remained high, the rate of sensitivity to penicillin was relatively high, and the moxifloxacin and levofloxacin-resistant strains had appeared; S. pneumoniae mainly showed QRDR mutations in gyrA, parE, and parC; and it was confirmed that S. pneumoniae can generate biofilms in vitro.